2022
DOI: 10.1128/spectrum.01353-22
|View full text |Cite
|
Sign up to set email alerts
|

Discordance between HIV-1 Population in Plasma at Rebound after Structured Treatment Interruption and Archived Provirus Population in Peripheral Blood Mononuclear Cells

Abstract: Even with effective ART, HIV-1 persists at undetectable levels and rebounds in individuals who stop treatment. Cellular and anatomical reservoirs ignite viral rebound upon treatment interruption, remaining one of the key obstacles for HIV-1 cure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 105 publications
(132 reference statements)
0
3
0
Order By: Relevance
“…Multiple studies have investigated the associations between HIV reservoirs and RV, LLV, or rebound viruses after treatment interruption ( Kearney et al, 2015 ; Lu et al, 2018 ; Aamer et al, 2020 ; Liu et al, 2020 ; Cole et al, 2022 ; Hendricks et al, 2022 ). Relatively few identical sequences were detected between RV, LLV, or rebound virus and replication-competent viruses from quantitative viral outgrowth assay (QVOA) ( Bailey et al, 2006 ; Brennan et al, 2009 ; Anderson et al, 2011 ; Aamer et al, 2020 ), and in most subjects, rebound viruses and reservoir provirus did not show sequence linkages ( Bailey et al, 2006 ; Lu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have investigated the associations between HIV reservoirs and RV, LLV, or rebound viruses after treatment interruption ( Kearney et al, 2015 ; Lu et al, 2018 ; Aamer et al, 2020 ; Liu et al, 2020 ; Cole et al, 2022 ; Hendricks et al, 2022 ). Relatively few identical sequences were detected between RV, LLV, or rebound virus and replication-competent viruses from quantitative viral outgrowth assay (QVOA) ( Bailey et al, 2006 ; Brennan et al, 2009 ; Anderson et al, 2011 ; Aamer et al, 2020 ), and in most subjects, rebound viruses and reservoir provirus did not show sequence linkages ( Bailey et al, 2006 ; Lu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the main HIV reservoir is known to be in resting memory CD4+ T-cells, several studies have shown that a fraction of viral variants, detected either in residual viremia during therapy or at rebound after therapy interruption, is genetically distinct from virus present in T-cell subsets [3][4][5] . Myeloid cells, particularly monocytes and macrophages, have been described as active reservoirs driving persistent low-level HIV expression and contributing to viral replication during rebound [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…While the main HIV reservoir is known to be in resting memory CD4+ T-cells, several studies have shown that a fraction of viral variants, detected either in residual viremia during therapy or at rebound after therapy interruption, is genetically distinct from virus present in T-cell subsets. [3][4][5] Myeloid cells, particularly monocytes and macrophages, have been described as active reservoirs driving persistent low-level HIV expression and contributing to viral replication during rebound. [6][7][8][9][10] Monocytes are chronically activated during HIV infection, and are major mediators for the development of comorbidities related to inflammageing, and specifically cardiovascular diseases, neurocognitive disorder, and aging of the innate immune system.…”
Section: Introductionmentioning
confidence: 99%